1993
DOI: 10.1111/j.1751-1097.1993.tb09553.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Human Immunodeficiency Virus Promoter by Uva Radiation in Combination With Psoralens or Angelicins

Abstract: The effects of mono- and bifunctional furocoumarins plus UVA radiation (PUVA and related treatments) on the human immunodeficiency virus-1 (HIV-1) promoter were studied using HeLa cells stably transfected with the chloramphenicol acetyl transferase gene under the control of the HIV-1 promoter. The experiments were performed with three psoralens (5-methoxypsoralen, 5-MOP; 8-methoxypsoralen, 8-MOP; and 4'-aminomethyl-4,8,5'-trimethylpsoralen, AMT) and four angelicins (angelicin; 4,5'-dimethylangelicin, 4,5'-DMA;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…Our studies support the concept that UV exposure can activate HIV gene expression as shown previously in transfected or latently infected cells (1)(2)(3)(4)(5)(6), and demonstrate for the first time that UVB-inducible HIV activation occurs in skin of seropositive individuals. The mechanism by which UV activates HIV gene expression has not been elucidated precisely, although pathways involving NFB (20)(21)(22) and p38 MAP kinase (23-25) have been implicated.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our studies support the concept that UV exposure can activate HIV gene expression as shown previously in transfected or latently infected cells (1)(2)(3)(4)(5)(6), and demonstrate for the first time that UVB-inducible HIV activation occurs in skin of seropositive individuals. The mechanism by which UV activates HIV gene expression has not been elucidated precisely, although pathways involving NFB (20)(21)(22) and p38 MAP kinase (23-25) have been implicated.…”
Section: Discussionsupporting
confidence: 90%
“…Concern about a detrimental relationship between ultraviolet radiation and HIV infection was triggered by cell culture (1)(2)(3)(4)(5)(6) and transgenic animal studies (7)(8)(9) that have shown ul- ¶Posted on the website on 17 traviolet B (UVB), ultraviolet C and psoralens plus ultraviolet A (PUVA) treatments to upregulate HIV gene expression, activate latent HIV or promote HIV replication (or all of them). Alerted by these findings, clinical investigators studied serial cases of HIV-infected patients treated for psoriasis, eosinophilic folliculitis or pruritus, with either UVB phototherapy or PUVA photochemotherapy (10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that PUVA can activate the HIV promoter in HIVcarMeLa cells (12). The UVA light dose response and kinetics of the HIV promoter activation are shown in Fig.…”
Section: Resultsmentioning
confidence: 88%
“…The specific therapeutic efficacies of MAs and ICLs are not well characterized. Zmudzka et al (20) have studied how the incident dose required for angelicins to induce 10% HIV promoter activity induction correlates to the DNA binding constant (20). Angelicins are limited by their structures to the formation of monoadducts.…”
Section: Discussionmentioning
confidence: 99%